Separated or Combined Treatment of Dye Wastewater Streams: A Case Study with Coagulation and Flocculation Process - Hoang Oanh, Le Thi; Le, Tran Nhat; Loan, Luu Minh; Quan, Nguyen Truong (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 1DO - 10.25073/2588-1094/vnuees.5000, 2024)
This study compared the treatment conditions and efficiencies of the coagulation and flocculation process (CFP) on mixed and separated dye wastewater. The CFP, which employed Poly Aluminium Chloride (PAC) as coagulant and mucilage extracted from the peel of dragon fruit ( Hylocereus undatus ) (DFPM) as flocculant, was investigated based on Jar-tests. The suitable coagulation and flocculation conditions were found similar at pH (4-7), settling time (30-60 min.), and flocculant dosage (2-5 mg/L) for both type of wastewaters. However, the optimal PAC dosage was determined to be significantly higher for separated dye wastewater stream (330 mg/L PAC) than for the mixed one (260 mg/L PAC) to ensure same treatment efficiencies. The treatment efficiencies were similar for TSS and turbidity of both wastewater types; However, much less for color and COD of separated dye wastewater stream in comparison to those of the mixed one (78% and 68% vs 90% and 76%, respectively). This study provides a scientific basis for the consideration of separated or combined treatment of dye wastewater streams by CFP.